XB130, a Novel Adaptor Protein, Promotes Thyroid Tumor Growth - Shiozaki, Atsushi (American Society for Investigative Pathology, 2011)
Adaptor proteins with multimodular structures can participate in the regulation of various cellular functions. We have cloned a novel adaptor protein, XB130, which binds the p85α subunit of phosphatidyl inositol 3-kinase and subsequently mediates signaling through RET/PTC in TPC-1 thyroid cancer cells. In the present study, we sought to determine the role of XB130 in the tumorigenesis in vivo and in related molecular mechanisms. In WRO thyroid cancer cells, knockdown of XB130 using small interfering RNA inhibited G(1)-S phase progression, induced spontaneous apoptosis, and enhanced intrinsic and extrinsic apoptotic stimulus-induced cell death. Growth of tumors in nude mice formed from XB130 shRNA stably transfected WRO cells were significantly reduced, with decreased cell proliferation and increased apoptosis. Microarray analysis identified 246 genes significantly changed in XB130 shRNA transfected cells. Among them, 57 genes are related to cell proliferation or survival, including many transcription regulators. Ingenuity Pathway Analysis showed that the top-ranked disease related to XB130 is cancer, and the top molecular and cellular functions are cellular growth and proliferation and cell cycle. A human thyroid tissue microarray study identified expression of XB130 in normal thyroid tissue as well as in human thyroid carcinomas. These observations suggest that the expression of XB130 in these cancer cells may affect cell proliferation and survival by controlling the expression of multiple genes, especially transcription regulators.